Aptamer-conjugated and doxorubicin-loaded unimolecular micelles for targeted therapy of prostate cancer - Xu, Wenjin (2013)
In the absence of effective therapy for prostate cancer, there is an immense need for developing improved therapeutic options for the management of this disease. This study has demonstrated that aptamer-conjugated unimolecular micelles can improve the in vivo tumor biodistribution of systemically administered anti-cancer drugs in prostate cancer expressing prostate-specific membrane antigen (PSMA). The aptamer-conjugated unimolecular micelles were formed by individual hyperbranched polymer molecules consisting of a hyperbranched H40 polymer core and approximately 25 amphiphilic polylactide–poly(ethlyene glycol) (PLA–PEG) block copolymer arms (H40-PLA-PEG-Apt). The unimolecular micelles with an average hydrodynamic diameter of 69 nm exhibited a pH-sensitive and controlled drug release behavior. The targeted unimolecular micelles (i.e., DOX-loaded H40-PLA-PEG-Apt) exhibited a much higher cellular uptake in PSMA positive CWR22Rν1 prostate carcinoma cells than non-targeted unimolecular micelles (i.e., DOX-loaded H40-PLA-PEG), thereby leading to a significantly higher cytotoxicity. The DOX-loaded unimolecular micelles up-regulated the cleavage of PARP and Caspase 3 proteins and increased the protein expression of Bax along with a concomitant decrease in Bcl2. These micelles also increased the protein expression of cell cycle regulation marker P21 and P27. In CWR22Rν1 tumor-bearing mice, DOX-loaded H40-PLA-PEG-Apt micelles (i.e., targeted) also exhibited a much higher level of DOX accumulation in the tumor tissue than DOX-loaded H40-PLA-PEG micelles (i.e., non-targeted). These findings suggest that aptamer-conjugated unimolecular micelles may potentially be an effective drug nanocarrier to effectively treat prostate cancer.